The Role of the Indonesian Air Force Health Service in Enhancing Integrated Air Medical Evacuation Capabilities to Support Military Operations Other Than War - Yudhitya Meglan; Sovian Aritonang; Budi Santoso (CV. AFDIFAL MAJU BERKAH, 2026)
Purpose – This article aims to examine the role of the Indonesian Air Force Health Service (Diskesau) in enhancing integrated air medical evacuation capabilities to support Military Operations Other Than War (MOOTW). The focus lies on strengthening doctrine, human resources, interoperable medical infrastructure, and civil–military collaboration to ensure rapid and effective humanitarian responses. Design/methodology/approach – This study employs a qualitative descriptive method using a Systematic Literature Review (SLR) approach. Relevant scientific literature and regulatory documents from 2018–2025 were collected from Scopus, Springer, ScienceDirect, Garuda, and ResearchGate. Twenty-nine primary sources were analyzed through thematic coding and triangulation to ensure reliability and validity. Findings – The study shows that: (1) Diskesau’s aeromedical evacuation doctrine is central to bridging military readiness and humanitarian operations, though it requires modernization and standardization (Frassini & Kral, 2022; NATO, 2021); (2) capability enhancement is strongly influenced by specialized training in aeromedicine, disaster medicine, and interoperability exercises with civilian agencies (Bulger et al., 2025; Sitorus & Wulandari, 2024); (3) modernization of air platforms such as C-130 Hercules, CN-295, and rotary-wing assets enables airborne intensive care units (AICU), though challenges remain in maintenance and spectrum of use (Ely et al., 2024; Roussignol et al., 2024); (4) civil–military cooperation with BNPB, Basarnas, and the Ministry of Health is essential for joint operations in disaster and crisis scenarios (WHO, 2023; PAHO, 2025). Practical implications – The effectiveness of air medical evacuation in MOOTW can be improved through the development of standardized aeromedical evacuation modules, regular joint exercises, digital integration with national health information systems, and quantitative performance metrics to evaluate readiness and response time (Peksa & Krüger, 2023; Risko et al., 2023). Originality/value – This article contributes by integrating doctrinal, technological, medical, and organizational perspectives into a unified framework for air medical evacuation. It strengthens the role of Diskesau in bridging military health operations with national disaster response, thereby enhancing Indonesia’s defense diplomacy and humanitarian credibility at both national and international levels Gates (2022).